The Legal Force Of Interfaith Marriage In Indonesia - Novea Elysa Wardhani (Journal Of Social Science (JoSS), 2023)
religions to obtain legality, but the existence of the life of a pair of people of different religions as husband and wife is a reality that cannot be denied in fact, many couples want to live together as husband and wife but are constrained to different religions or beliefs. Some choose a way of life to be together without marriage ties or "cohabitation" while still maintaining their respective religions and beliefs. This situation is still allowed to exist without a solution or their behavior is considered as community waste which must be approached with a controlling approach. Then what about the consequences of their relationship that are not protected by the laws in force in this country, such as the existence of offspring that are born, the assets that are generated, and other rights? This problem will not be a solution if the marriage of interfaith couples is not registered by the authorized institution.